INOVASI PELAYANAN ADMINISTRASI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PINRANG - Irma, Irma; Malik, Ihyani; Pratama, Muhammad Randy (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This research aims to analyze public service innovation through UP3SK at the Pinrang Regency Population and Civil Registration Service. This research is qualitative research, the research carried out is descriptive. The results of the research show that public service innovation through UP3SK at the Pinrang Regency Population and Civil Registration Service can be seen based on innovation attributes according to Rogers. In the "five attributes of innovations" relative advantage, it is known that the advantages of UP3SK service innovation minimize the practice of brokering and make things easier for the community. The compatibility attribute explains that the service innovation is in accordance with the wishes of the community in terms of an easier document processing process. The complexity attribute explains that there is no complexity in the management and also in the UP3SK service process. The triability attribute also explains that there is no trial phase for the community in the UP3SK service. Observability shows that as long as the UP3SK service is running, it is in accordance with the wishes of the Pinrang Regency Population and Civil Registration Service